Biomechanical analysis for the IAAF World Championships London 2017 200 m Women's - Pollitt, L.; Walker, J.; Tucker, C.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2018)
Dafne Schippers added to her bronze medal from the 100 m by defending her 200 m world title on the evening of Friday 11th August; despite being only sixth on the 2017 world list (22.10 s). While a season`s best time of 22.05 s secured the gold, she was made to work by the Ivorian Marie-Josée Ta Lou. After both made excellent starts, Schippers led by the slightest of margins at the bend. Despite a strong finish, Ta Lou, once again narrowly missed out on the gold medal. And despite being just 0.04 s away from two World Championship gold medals, her mark of 22.08 s set a new national record. In the battle for the bronze medal, Great Britain`s Dina Asher-Smith headed the remainder of the field into the home straight. In spite of the tremendous roar from the home crowd, she couldn`t hold off the challenge of Shaunae Miller-Uibo, who claimed bronze in 22.15 s. While this may have been somewhat of a consolation for Miller-Uibo, after disappointment in the 400 m, for Asher-Smith, finishing fourth in a season`s best of 22.22 s, the joint third fastest time of her career, was remarkable considering she broke a bone in her foot in February and only began her season in late June.